ANALISIS YURIDIS TERHADAP TANGGUNG JAWAB LAYANAN CHATBOT BERBASIS AI DALAM PELINDUNGAN KONSUMEN DI ERA DIGITAL - Rudi Hartono; Syamsul Efendi; Eka Pratiwi; Jenggis Khan Haikal; Subagio (RESTORATIVE JUSTICE : Jurnal Hukum Universitas Muhammadiyah Kalianda, 2025)
The rapid adoption of artificial intelligence (AI)-based chatbots in consumer services has given rise to new challenges: inaccuracies (hallucinations), misleading advice, manipulation of consumer choices (dark patterns), breaches of personal data, and difficulties in enforcing liability when harm occurs. This article examines the legal basis for assigning liability to business actors (AI chatbot providers and deployers) using a doctrinal-comparative approach: Indonesian law (Law No. 8/1999 on Consumer Protection; Law No. 27/2022 on Personal Data Protection) compared with developments in the European Union regime (EU AI Act; Digital Services Act) and oversight practices in the United States (FTC). The main findings are: (1) the general framework of business actor liability under the Consumer Protection Law remains relevant to address misrepresentation/negligence in AI-based services; (2) the transparency obligations and risk governance provisions in the EU AI Act provide a “due diligence” model that can be adopted both privately and through regulation; (3) consumer protection authorities should interpret “unfair/misleading practices” to include chatbot interface design and output; (4) the Personal Data Protection Law clarifies the legal basis for the processing of personal data by chatbots. Recommendations: a national guideline specifically for consumer chatbots, mandatory “safety by design” and audit mechanisms, standardized incident notification/handling procedures, as well as compensation and evidence mechanisms based on conversation logs/records.